AKSESIBILITAS TRANSPORTASI BAGI PENGGUNA KURSI RODA DI TRANSIT ORIENTED DEVELOPMENT DUKUH ATAS - Handojo Putra, Raynaldi; Putranto, Leksmono Suryo (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
Development in Indonesia continues to increase rapidly, especially in the capital city of Jakarta, there are many activities carried out by people in the capital city. The development of activities in the capital city of Jakarta itself needs to be carried out using public transportation. Public transportation itself is an investment to transport large numbers of passengers. Passengers in public transportation themselves have two categories of priority and non-priority passengers. The priority passengers are people with disabilities who use public transportation services themselves. This paper aims to describe the real situation of transportation accessibility needs for wheelchair users in the transit-oriented development of Dukuh Atas Sudirman Jakarta using several methods such as validity tests, reliability tests, homogeneity tests, one sample T-Test & Independent sample T-Test. The research results show that there is a lack of supporting facilities such as lifts and ramps that help people with disabilities to carry out mobility in the Dukuh Atas transit-oriented development area.